Analysis and Prediction on the Current Situation of the Repair Class and Repair System of Electric Multiple Units (EMU) - ZHOU Bin; XIE Minyuan; WU Keming (机车电传动)
The development of modern railway equipment maintenance system was reviewed, detailed in the current condition and defects of EMU maintenance system, and the disadvantages of periodic maintenance such as insufficient repair, excessive repair, high risk of secondary disasters, and high cost of maintenance were pointed out. Then, the application of condition based maintenance (CBM) in EMU was analyzed and demonstrated. Lastly, the logic decision flow chart of EMU maintenance was proposed and the development trends of EMU maintenance system in the future were prospected.